Association of the Eukaryotic Vaginal Virome with Prophylactic Antibiotic Exposure and Reproductive Outcomes in a Subfertile Population Undergoing In Vitro Fertilization: A Prospective Exploratory Study - Eskew, Ashley M. (BJOG, 2019)
OBJECTIVE: The objective of this study was to use high-throughput sequencing to describe the vaginal eukaryotic DNA virome in patients undergoing in vitro fertilization (IVF) to examine associations between the vaginal virome, antibiotic exposure, and IVF outcomes. DESIGN: Prospective exploratory study SETTING: Single Academic Fertility Center POPULATION: Subfertile women age 18–43 undergoing their first IVF cycle with a fresh embryo transfer. METHODS: The primary exposure was prophylactic azithromycin or no azithromycin prior to IVF. Patients had a mid-vaginal swab obtained at the time of embryo transfer for virome analysis. MAIN OUTCOME MEASURES: The primary outcome compared between exposure groups was characteristics of vaginal virome and clinical pregnancy rates. Secondary outcomes were virome associations with number of oocytes retrieved, number of blastocysts, and implantation rate. RESULTS: Twenty-six subjects contributed a vaginal swab prior to embryo transfer. There were no significant differences in IVF outcomes between azithromycin groups. There was no association between viral diversity and clinical pregnancy overall. A higher diversity of herpesviruses and alphapapillomaviruses were observed in samples from the azithromycin-treated group compared to the no azithromycin group (p=0.04). In subjects that received azithromycin, viral diversity was higher in the group that did not achieve clinical pregnancy compared to those who did (p=0.06). CONCLUSIONS: We demonstrate the vaginal eukaryotic virome in women undergoing IVF is associated with antibiotic exposure. Additionally, we demonstrate an inverse trend between viral diversity and pregnancy, with a higher number of viruses detected associated with failure to achieve clinical pregnancy in the azithromycin group.